2010 4th International Conference on Bioinformatics and Biomedical Engineering 2010
DOI: 10.1109/icbbe.2010.5516579
|View full text |Cite
|
Sign up to set email alerts
|

Adhesive and In Vitro Release Properties of the Konjac Glucomannan and Xanthan Gum Mixture Gel Film

Abstract: Purposes: To study the adhesive and the in vitro release properties of a mixture gel film prepared with two kinds of natural polysaccharides -konjac glucomannan and xanthan gum. Methods: The optimal formula was investigated by the quadratic regression rotatable orthogonal design with adhesive force as the evaluated parameter. Its in vitro release behavior was studied by the in vitro accumulative released curve with aciclovir as the model medicine. Results: By predication and verification, the optimal formula f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Synergistic reaction between KGM and other polysaccharide is another method for preparing KGM-based hydrogels, KGM-κ-carrageenan and KGM-xanthan gum (XG) hydrogels had been reported in previous researches, but their microstructure had not reported [ 39 , 40 , 41 , 42 ]. Zhang et al [ 43 ] used two natural polysaccharides—KGM and XG—to prepare a mixed gel film for use as a matrix material for mucosal adhesives and transdermal drug delivery systems. Estimation and experimental verification suggested that the optimum formulation was as follows: 50 mL of 1% ( w / w ) KGM and 1% ( w / w ) XG solution were used to prepare the mixed gel at a ratio of 2.36:1 ( v / v ).…”
Section: Preparation Of Konjac Glucomannan (Kgm) Gel and Its Micromentioning
confidence: 99%
“…Synergistic reaction between KGM and other polysaccharide is another method for preparing KGM-based hydrogels, KGM-κ-carrageenan and KGM-xanthan gum (XG) hydrogels had been reported in previous researches, but their microstructure had not reported [ 39 , 40 , 41 , 42 ]. Zhang et al [ 43 ] used two natural polysaccharides—KGM and XG—to prepare a mixed gel film for use as a matrix material for mucosal adhesives and transdermal drug delivery systems. Estimation and experimental verification suggested that the optimum formulation was as follows: 50 mL of 1% ( w / w ) KGM and 1% ( w / w ) XG solution were used to prepare the mixed gel at a ratio of 2.36:1 ( v / v ).…”
Section: Preparation Of Konjac Glucomannan (Kgm) Gel and Its Micromentioning
confidence: 99%
“…It consists of random distribution of β-(1-4)-linked D-glucose and β-(1-4)-linked D-mannose in the backbone (Figure 4) (Gopinath et al, 2018). Zhang et al(2010) fabricated gel film of acyclovir with konjac glucomannan and xanthan gum. The optimized film composed of konjac glucomannan and xanthan gum at a ratio 2.36:1 (v/v) displayed optimal adhesive ability.…”
Section: Glucomannansmentioning
confidence: 99%
“…The optimized film composed of konjac glucomannan and xanthan gum at a ratio 2.36:1 (v/v) displayed optimal adhesive ability. The release of the drug from the optimized film showed a peak at 4.5 h and could maintain for 3-7 h. Thus, the above film had good bioadhesive property along with controlled-release abilities (Zhang et al, 2010). Types of polysaccharides with various formulations, incorporated drugs, and used for the treatment are presented in Table I.…”
Section: Glucomannansmentioning
confidence: 99%